Case report of acquired pyroglutamic acidemia in a pediatric patient - Bischoff, Adrianne Rahde; Dornelles, Alícia Dorneles; de Azevedo, Ana Luiza Tainski; Chakr, Valentina (Clinical and Biomedical Research, 2015)
Pyroglutamic acid (also known as 5-oxoproline) is an organic acid intermediate of the gamma-glutamyl cycle. Accumulation of pyroglutamic acid is a rare cause of high anion gap metabolic acidosis. In the pediatric population, the congenital form of pyroglutamic acidemia has been extensively described. However, there are scarce reports of the acquired form of this condition in children. The urine test for organic acids confirms the diagnosis of pyroglutamic acidemia. We report the case of a 16-month-old girl who developed transient 5-oxoprolinemia associated with malnutrition and the use of acetaminophen and ampicillin for the treatment of acute otitis media and abdominal pain. The patient received 21-hour course of n-acetylcysteine with improvement of metabolic acidosis. This report highligts the need of considering pyroglutamic acidemia in the differencial diagnosis for high anion gap metabolic acidosis in pediatric patients with malnutrition and other risk factors.